Philip Larkin - Booth, J. author. aut Link
IX, 230 p.
Keywords: James Booth reads Philip Larkin's mature poetry in terms of his ambiguous self-image as lonely, anti-social outsider, plighted to his art, and as nine-to-five librarian, sharing the common plight of humanity. Booth's focus is on Larkin's artistry with words, the 'verbal devices' through which this purest of lyric poets celebrates 'the experience. The beauty.' Featuring discussion for the first time of two recently discovered poems by Larkin, this original and exciting new study will be of interest to all students, scholars and enthusiasts of Larkin.